A Multimodal Approach to the Osseointegration of Porous Implants - Deering, Joseph (My University, 2022)
The field of implantology is centred around interfacial interactions with the surrounding bone tissue. Assessing the suitability of novel engineering materials as implants for clinical application follows a preliminary workflow that can be simplified into three main stages: (i) implant design, (ii) in vitro compatibility, and (iii) in vivo compatibility. This thesis is subdivided to mirror each of these three themes, with a specific focus on the multiscale features of the implant itself as well as appositional bone tissue. In Chapter 3, a biomimetic approach to generate porous metallic implants is presented, using preferential seeding in a 3D Voronoi tessellation to create struts within a porous scaffold that mirror the trabecular orientation in human bone tissue. In Chapter 4, cytocompatible succinate-alginate films are generated to promote the in vitro activity of osteoblast-like cells and endothelial cells using a methodology that could be replicated to coat the interior and exterior of porous metals. In Chapter 5, two types of porous implants with graded and uniform pore size are implanted into rabbit tibiae to characterize the biological process of osseointegration into porous scaffolds. In Chapter 6, these same scaffolds are probed with high-resolution 2D and 3D methods using scanning transmission electron microscopy (STEM) and the first-ever application of plasma focused ion beam (PFIB) serial sectioning to observe structural motifs in biomineralization at the implant interface in 3D. This thesis provides new knowledge, synthesis techniques, and development of characterization tools for bone-interfacing implants, specifically including a means to: (i) provide novel biomaterial design strategies for additive manufacturing; (ii) synthesize coatings that are compatible with additively manufactured surfaces; (iii) improve our understanding of mineralization process in newly formed bone, with the ultimate goal of improving the osseointegration of implants.
Keywords: bone; biomaterials; electron microscopy; additive manufacturing